Interaksi Sosial dan Praktik Keagamaan dalam Program Tahsin Daring: Studi Sosiologis atas Majelis Fathimah Karimah - Muhammad Hizba Aulia; Wawan Hermawan; Fadhilah Sukmawati Tanjung (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
This study examines the social dynamics of online tahsin learning, with a primary focus on patterns of social interaction and the formation of participants’ religious habits at Majelis Fathimah Karimah as a non-formal religious institution adopting a digital learning model. The main concern of this study is how social interaction and religious habits are formed and transformed within an online learning environment. Employing a qualitative descriptive approach, data were collected through semi-structured and in-depth interviews, questionnaires, digital documentation and participatory observation of online learning interactions. The findings indicate that the online tahsin program successfully fosters strong social bonds, encourages active participation and facilitates participants’ religious transformation. Online platforms such as Zoom and WhatsApp enable direct recitation feedback, emotional connection and peer support. Social interaction occurs not only explicitly through dialogue but also implicitly through shared learning experiences. The program also cultivates new religious habits, including consistent Qur’anic recitation, group-based motivation and personal development. Nevertheless, challenges such as unstable internet connectivity and the absence of a formal attendance system remain obstacles to program implementation. Overall, this study concludes that online tahsin programs can serve as transformative spaces for religious education, in which technology supports cognitive achievement alongside the strengthening of social and spiritual dimensions.